A novel approach to assessing validity in sports performance research: integrating expert practitioner opinion into the statistical analysis - Kyprianou, E.; Lolli, L.; AI Haddad, H.; Di Salvo, V.; Varley, C. M.; Villanueva, M. A.; Gregson, W.; Weston, M. (Science and Medicine in Football, 2019)
Purpose: Using elite youth soccer players' maximal sprinting speeds collected from a criterion and non- criterion measure, we demonstrate how expert practitioner opinion can be used to determine mea- surement validity.